The HDAC6 Inhibitor Trichostatin A Acetylates Microtubules and Protects Axons From Excitotoxin-Induced Degeneration in a Compartmented Culture Model - Hanson, Kelsey; Tian, Nan; Vickers, James C.; King, Anna E. (Frontiers in Neuroscience, 2018)
Axon degeneration has been implicated as a pathological process in several neurodegenerative diseases and acquired forms of neural injury. We have previously shown that stabilising microtubules can protect axons against excitotoxin-induced fragmentation, however, the alterations to microtubules following excitotoxicity that results in axon degeneration are currently unknown. Hence, this study investigated whether excitotoxicity affects the post-translational modifications of microtubules and microtubule-associated proteins, and whether reversing these changes has the potential to rescue axons from degeneration. To investigate microtubule alterations, primary mouse cortical neurons at 10 days in vitro were treated with 10µM or 25µM kainic acid to induce excitotoxicity and axon degeneration. Post-translational modifications of microtubules and associated proteins were examined at 6 hours following kainic acid exposure, relative to axon degeneration. While there were no changes to tyrosinated tubulin or MAP1B, acetylated tubulin was significantly (p<0.05) decreased by 40% at 6 hours post-treatment. To determine whether increasing microtubule acetylation prior to kainic acid exposure could prevent axon fragmentation, we investigated the effect of reducing microtubule deacetylation with the HDAC6 inhibitor, trichostatin A. We found that trichostatin A prevented kainic acid-induced microtubule deacetylation and significantly (p<0.05) protected axons from fragmentation. These data suggest that microtubule acetylation is a potential target for axonal protection where excitotoxicity may play a role in neuronal degeneration.